PENINGKATAN SKILL MENULIS ABSTRAK BAHASA INGGRIS MELALUI PEMBELAJARAN REVIEW BUKU BAGI SANTRI FLASHROOM - Nur Rokhmatulloh; Aminatuz Zuhriah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
Writing requires language structure, graphology, and vocabulary skills. Improving students' writing skills requires a creative approach and continuous practice. One type of writing skill that students need to master is abstract writing. Writing abstracts through book reviews is a fun alternative learning approach for students. This approach is very helpful for the students of Pesantren Ngalah about how to write abstracts easily. This research uses classroom action research method. With this method, it is possible to know in detail the problems in the classroom, and how to solve them. This study aims to provide recommendations to teachers as learning evaluation materials. Thus, it is hoped that the quality of learning will be better. Based on the results of the study that students were able to write abstracts properly and correctly with the percentage level of the high category interval 60%, the medium category 26.67%, and the low category 13.33%.